Design and performance evaluation of a powered stapler for gastrointestinal anastomosis. Issue 4 (1st April 2022) - Wang, Haochen; Ge, Wenming; Liu, Chenxu; Wang, Peiyao; Song, Chengli
Abstract: Objective: This paper reports the design of a powered stapler for gastrointestinal anastomosis and evaluates its performance. The proposed stapling instrument is intended to simplify and optimize the current procedure of mechanical stapling, while providing controllable operation for the powered stapling procedure, such as conditioning the tissue to the right stage before firing of the stapler. Material and methods: The feasibility and efficacy of the prototype were assessed by ex vivo experiments with porcine small intestine segments, where the tissue conditioning operation, burst pressure of the stapled intestine samples, and staple malformation rate were examined. Results: The functionality of the developed powered stapler was validated, where the theoretical, numerical, and experimental results agree well with each other. The preliminary results indicated that the proposed tissue conditioning operation could lower the clamping pressure with a maximum level of 1.35 g/mm 2 . The average burst pressure of the stapled segments (16 samples) is 6.37 kPa, and the maximum malformation rate of the tested groups (five groups, each group with 90 staplers) was 5.56%. Conclusion: The developed novel tissue conditioning procedure could reduce the pressure response of the intestine tissue samples. The proposed powered stapler proves effective for performing gastrointestinal anastomosis procedures.